TAREKAT SYEIKH MUHAMMAD ARSYAD AL-BANJARI: TELAAH ATAS KITAB KANZ AL-MA'RIFAH - Abdul Hadi (Pascasarjana UIN ANTASARI Banjarmasin, 2011)
Development of Sufism in the archipelago is one icon in view of the problems connected with the Sufi. Sufism is the diversity of colour patterns of thought of religious life, while religious practice to be a representation of the diversity of religious thought to be highly variable and often decorated with the interview